Intelligent innovative regulatory tools on financial technology:concept,platform framework,and prospects - Hongfeng CHAI; Shuai WANG; Xiaojun TU; Quan SUN; Xiaofeng MA; Jie WU; Hua CAI; Xiaolong ZHENG; Fei-Yue WANG (智能科学与技术学报)
In view of the complex and severe challenges faced by financial technology regulation and the lag behind situation of the existing regulatory sandbox which is highly dependent on manual operation,the important feature and development trend of the Chinese “innovative regulatory tools on financial technology” lie in “intelligence” were pointed out.A systematic platform framework of “intelligent innovative regulatory tools on financial technology” was proposed,that is,use modern means of science and technology to realize the full life cycle supervision of financial technology innovative applications.The elements of innovative regulatory tools were elaborated,including the underlying blockchain,public opinion monitoring platform,explainable artificial intelligence based on knowledge graphs,and presented the key technologies involved.The new iterative methodology used in the development of the innovative regulatory tools platform was introduced,i.e.,the spiral development model and iterative design driven by the hierarchy of needs.Towards the end,some thoughts and prospects on the proposed innovative regulatory tools were put forward,and the regulatory tools are expected to create a set of regulatory technology infrastructure to serve regulatory authorities and financial institutions were pointed out.